Electro-Optical Property of Plasma Enhanced Chemical Vapor Deposition ZnO:Al Films Influenced by Substrate Materials and Annealing Treatments - Hong, Lingli; Chen, Zhaoquan; Xue, Changguo; Cheng, Wei; Bai, Yang; Li, Huihui; Liu, Minghai; Hu, Xiwei (Asian Journal of Chemistry, 2014)
In this paper, AZO (ZnO:Al) polycrystalline thin films with strong adhesion to the substrate, as low as 89 W/% of square resistance and as high as 85 % of visible light transmittance, have been fabricated by PECVD (plasma enhanced chemical vapor deposition) method depositing on glass substrate and silicon substrate, respectively. Based on PECVD method, the electro-optical property of the proposed AZO films influenced by substrate materials and annealing treatments is studied in detail. the fabrication process of AZO film is also shown. The results suggested that AZO film fabricated by PECVD is a meaningful attempt for the industrial applications.